2007
DOI: 10.1074/jbc.m704102200
|View full text |Cite
|
Sign up to set email alerts
|

Asparaginyl Hydroxylation of the Notch Ankyrin Repeat Domain by Factor Inhibiting Hypoxia-inducible Factor

Abstract: The stability and activity of hypoxia-inducible factor (HIF) are regulated by the post-translational hydroxylation of specific prolyl and asparaginyl residues. We show that the HIF asparaginyl hydroxylase, factor inhibiting HIF (FIH), also catalyzes hydroxylation of highly conserved asparaginyl residues within ankyrin repeat (AR) domains (ARDs) of endogenous Notch receptors. AR hydroxylation decreases the extent of ARD binding to FIH while not affecting signaling through the canonical Notch pathway. ARD protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
245
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 198 publications
(258 citation statements)
references
References 32 publications
12
245
1
Order By: Relevance
“…These observations agree with a previous study suggesting that Notch signaling is increased in hypoxia through the direct interaction between the intracellular Notch receptor domain N ICD and HIF-1 (24). We speculate that increased N ICD levels through Jagged2 expression could reciprocally inhibit factor-inhibiting HIF (FIH) and augment HIF function to provide a hypoxic growth advantage independent of Notch target genes (30). Further evidence suggests that N ICD enhances HIF1 recruitment to its target gene promoters, resulting in increased HIF1 activity in vitro (23).…”
Section: High Myc State Increases Notch Signaling Components With Jagsupporting
confidence: 82%
“…These observations agree with a previous study suggesting that Notch signaling is increased in hypoxia through the direct interaction between the intracellular Notch receptor domain N ICD and HIF-1 (24). We speculate that increased N ICD levels through Jagged2 expression could reciprocally inhibit factor-inhibiting HIF (FIH) and augment HIF function to provide a hypoxic growth advantage independent of Notch target genes (30). Further evidence suggests that N ICD enhances HIF1 recruitment to its target gene promoters, resulting in increased HIF1 activity in vitro (23).…”
Section: High Myc State Increases Notch Signaling Components With Jagsupporting
confidence: 82%
“…All these proteins contain ankyrin-repeat domains (ARDs) and include IkBa; p105; Notch1, 2 and 3; and Ankyrin repeat and SOCS Box protein 4 (ASB4). [44][45][46] Presently, the function of hydroxylation on these novel substrates remains unclear, with only subtle downstream effects, if any, being observed. However, it has been suggested that hydroxylation of ARD-containing proteins occurs in competition with HIF hydroxylation, and could potentially regulate HIF-mediated transcription by sequestering FIH-1, particularly in hypoxia.…”
Section: Oxygen-dependent Regulation Of Hif-cad By Fih-1mentioning
confidence: 99%
“…However, it has been suggested that hydroxylation of ARD-containing proteins occurs in competition with HIF hydroxylation, and could potentially regulate HIF-mediated transcription by sequestering FIH-1, particularly in hypoxia. 45 …”
Section: Oxygen-dependent Regulation Of Hif-cad By Fih-1mentioning
confidence: 99%
“…Importantly, mass spectroscopic evidence for hydroxylation of ankyrin repeats in IkB and nuclear factor kB family members, as well as in ASB4, a suppressor of cytokine signaling, by FIH showed that hydroxylation is not restricted to HIF-a subunits (Coleman et al, 2007;Ferguson et al, 2007). Although direct mass spectroscopic evidence for hydroxylation is missing, PHD1 and PHD3 have recently been shown to regulate IkB kinase-b and activating transcription factor-4, respectively (Cummins et al, 2006;Koditz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%